The Zeitgeist In Munir Niazi's Poems - Khizra Tabassum (بازیافت, 2023)
<span style="font-size: 15.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Munir Niazi holds a rank among the poets of modern era. He set new standards for Urdu verse. His poetry contracts with terror, emptiness and trance yet innocence, beauty and grace also devise his style. The reader finds peace and hope in his poems as he was a man from the real world instead of a mere poet lost in an imaginary world. Thus, the current article seeks to study Munir Niazi as a poet of nature and life.